DETERMINASI SOSIAL LINGKUNGAN KERJA DAN EPIDEMIOLOGI PSIKOSOSIAL: TINJAUAN LITERATUR DAMPAK SHIFT KERJA DAN BEBAN KERJA TERHADAP KINERJA MELALUI MEDIASI BURNOUT ‘PADA PERAWAT DI RSUD PROVINSI NTB - Muhammad Munip; Yuly Peristiowati (Jurnal Cakrawala Ilmiah, 2026)
Background: Nurses at the NTB Provincial General Hospital face significant psychosocial challenges due to high work demands in a primary referral facility. Objective: This study aims to analyze the social determination of the work environment, specifically the impact of work shifts and workload on nursing performance through the mediation of burnout from a psychosocial epidemiology perspective. Methods: This study employed a Narrative Literature Review method. Literature searches were conducted through Scopus and Google Scholar databases covering the period 2015-2025. Articles the inclusion criteria were synthesized to provide a comprehensive overview of the phenomenon. Results: Findings indicate that non-ergonomic work shifts and excessive workload are primary predictors of burnout among nurses. Burnout consistently mediates the relationship between work environment pressures and the decline in clinical performance and work motivation. Conclusion: The decline in nursing performance at the NTB Provincial General Hospital is a manifestation of unmanaged psychosocial stressors. Hospital management needs to intervene in work schedule systems and workload distribution to reduce burnout rates and maintain the quality of healthcare services